Exploring post-SEPSIS and post-COVID-19 syndromes: crossovers from pathophysiology to therapeutic approach - Holmes, Darcy; Colaneri, Marta; Palomba, Emanuele; Gori, Andrea (Frontiers in Medicine, 2024)
Sepsis, driven by several infections, including COVID-19, can lead to post-sepsis syndrome (PSS) and post-acute sequelae of COVID-19 (PASC). Both these conditions share clinical and pathophysiological similarities, as survivors face persistent multi-organ dysfunctions, including respiratory, cardiovascular, renal, and neurological issues. Moreover, dysregulated immune responses, immunosuppression, and hyperinflammation contribute to these conditions. The lack of clear definitions and diagnostic criteria hampers comprehensive treatment strategies, and a unified therapeutic approach is significantly needed. One potential target might be the renin-angiotensin system (RAS), which plays a significant role in immune modulation. In fact, RAS imbalance can exacerbate these responses. Potential interventions involving RAS include ACE inhibitors, ACE receptor blockers, and recombinant human ACE2 (rhACE2). To address the complexities of PSS and PASC, a multifaceted approach is required, considering shared immunological mechanisms and the role of RAS. Standardization, research funding, and clinical trials are essential for advancing treatment strategies for these conditions.